Proceedings of the 17th Annual International Conference on Mobile Computing and Networking 2011
DOI: 10.1145/2030613.2030647
|View full text |Cite
|
Sign up to set email alerts
|

Practical, real-time, full duplex wireless

Abstract: This paper presents a full duplex radio design using signal inversion and adaptive cancellation. Signal inversion uses a simple design based on a balanced/unbalanced (Balun) transformer. This new design, unlike prior work, supports wideband and high power systems. In theory, this new design has no limitation on bandwidth or power. In practice, we find that the signal inversion technique alone can cancel at least 45dB across a 40MHz bandwidth. Further, combining signal inversion cancellation with cancellation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
941
0
11

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,212 publications
(983 citation statements)
references
References 15 publications
(22 reference statements)
5
941
0
11
Order By: Relevance
“…Furthermore, the CHF of Z is independent of the angle between the real and imaginary components. Consequently, (4) shows that Z follows a circularly symmetric complex Laplace distribution. Theorem 1.…”
Section: Distribution Of the Intra-cell Interferencementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the CHF of Z is independent of the angle between the real and imaginary components. Consequently, (4) shows that Z follows a circularly symmetric complex Laplace distribution. Theorem 1.…”
Section: Distribution Of the Intra-cell Interferencementioning
confidence: 99%
“…FD communication relies on the recently developed self-interference (SI) cancellation techniques that enable simultaneous transmission and reception on the same frequency band, which offer better spectral utilization compared to the half-duplex (HD) system [3], [4]. However, implementing SI cancellation at the user's equipment (UE) can be expensive in terms of complexity, power consumption, and/or terminal price.…”
Section: Introductionmentioning
confidence: 99%
“…Avoiding the issue of the transmitting signal interfering with the receiving signal requires operation at either different times or at different frequencies. However, prospects for creating an in-band full-duplex system, which would allow for transmitting and receiving on the same frequency at the same time, have shown that full-duplex is feasible [1][2][3][4][5][6]. Ideally, this would allow twice as many devices to make use of a given spectrum at any time.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the self-interference needs to be suppressed before the RF front-end at the receiver. To combat this, three methods have been studied [5,6,7]. Antenna cancellation uses an additional transmitting antenna to form a null point at the receiving antenna [5].…”
Section: Introductionmentioning
confidence: 99%
“…Antenna cancellation uses an additional transmitting antenna to form a null point at the receiving antenna [5]. Balun cancellation places a balun circuit between the transmitting and receiving antennas to subtract the self-interference signals from the received signals [6]. Note that these methods cannot be directly applied to MIMO systems because the interference among all combinations of transmitting and receiving antennas must be considered and implementation is difficult.…”
Section: Introductionmentioning
confidence: 99%